ANALISIS SALURAN PEMASARAN TANDAN BUAH SEGAR (TBS) KELAPA SAWIT PADA PETANI SWADAYA DI DESA SIMPANG KELAYANG KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Ardiansyah Pratama; Eliza Eliza; Ermi Tety (Jurnal Ilmiah Pertanian, 2016)
This study aims to find and know, and analyze: 1) channels, marketing margin and part of the price received by farmers. 2) connection or correlation between the price of palm oil paid to the farmer MCC Organization. This study used survey method, with purposive sampling to farmers. Samples of plant age 7-10. with a determined 10% of the population so that the sample was taken 22 216 farmers. Samples traders and MCC using snowball sampling method. Desa Simpang Kelayang District of Kelayang there is a middleman that farmer-trader-MCC. Farmer selling price to wholesalers in February 2015 is Rp. 1326.36 / kg and traders selling to the MCC for Rp. 1790.64 / kg. Margin of March 2014- February 2015 were the highest month of January 2015 amounted to Rp. 420.26 / Kg. The lowest margin in April 2014 amounted to Rp. 125.40 / Kg TBS marketing Efficiency In February 2015 amounted to 14.28 percent of total marketing margin of USD 464.28 / Kg and part of farmers received 73.03 percent. price correlation values (r) at the level of farmers with traders amounted to 0.832